Public Intention on Bandung Tour on Bus - Tezza Adriansyah Anwar; Yessy Puspita (LPPM STMIK AMIK BANDUNG, 2020)
Bandung is known as the capital of West Java. Bandung also develops as a culinary city. As a form of the Government's responsibility to facilitate tourists who come to Bandung, the Government has officially announced the